PENGARUH SHOPEE PAYLATER DAN GAYA HIDUP TERHADAP PENGELOLAAN KEUANGAN MAHASISWA DI POLITEKNIK PAJAJARAN BANDUNG - Nur Rahma Khaliandri, Syalwa; Hatimatunnisani , Hani; Farina , Farin Taska; Salsabila , Kania Syalwa; Habiburahman , Fadil (Jurnal Sosio dan Humaniora (SOMA), 2025)
This study aims to analyze the effect of Shopee PayLater usage and lifestyle on financial management of college students. Shopee PayLater is one of the installment payment methods that is popular among Shopee users in Indonesia, especially among students. This research uses a quantitative approach with a survey as the data collection method. The research sample consisted of 50 students who actively use Shopee PayLater. The results showed that the use of Shopee PayLater has a positive effect on financial management while lifestyle has a negative effect on financial management. This show that with the ease of payment through Shopee PayLater, it is hoped that students can be more flexible in making purchases, but also has the potential to change their lifestyle with a tendency to increase consumption of non-priority items, and had a negative impact on students' financial management, especially in terms of financial discipline and spending control.